Hybrid renewable energy systems to supply electricity self-sufficient residential buildings in Central Europe. (February 2019) - Camargo, Luis Ramirez; Gruber, Katharina; Nitsch, Felix; Dorner, Wolfgang
Abstract: This work evaluates potentials of photovoltaic and battery systems with additional micro-generation wind turbines (10.5 kW) to cover electricity demand of residential users in two countries in Central Europe. It relies on high-resolution regional reanalysis data and a techno-economical optimization model. Maps showing the number of wind turbines, photovoltaic and battery systems sizes necessary to supply electricity for clusters of electricity self-sufficient single-family houses across Germany and the Czech Republic are generated. No general trends that apply for the two countries concerning the relation between the sizes of the different technologies were identified. However, it was possible to determine several large areas where the inclusion of small wind turbines decreases the total system costs and considerably reduces the required storage capacities. Results are discussed and compared to previous work on self-sufficient single-family houses.